Analisis Kebijakan Kualifikasi Kesehatan Dan Standar Pengawakan Terhadap Kinerja Awak Kapal Bedasarkan Penerapan MLC 2006 - Andri Yulianto; Kumila Hanik; Latifa Salsa Nabila (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
Maritime Labour Convention (MLC) 2006 is a standard level of manning when establishing, approving or revising the level of manning, the competent authority is obliged to pay attention to the need for working hours or minimize excess working hours, as well as the principles of applicable international instruments, in particular from the International Maritime Organization regarding the level of manning. The purpose of this study is to analyze health qualification policies and manning standards for crew performance based on the application of MLC 2006 in PT. Dhama Lautan Utama Semarang Branch. The method used in this study was descriptive qualitative where the sample used was 6 people. The data analysis technique uses the SWOT analysis method using the calculation process of IFAS (Internal Strategy Factor Analysis), EFAS (External Strategy Factor Analysis) and SWOT Analysis diagram using a likert model scale. Based on the results of the analysis, it shows that there are internal and external influences on health qualification policies and manning standards on the performance of ship crews based on the 2006 Maritime Labour Convention (MLC) in PT. Dharma Lautan Utama, Semarang branch. Using SWOT IFAS and EFAS analysis in the calculation of external factors, the value is 0.667 internal while internal factors of 1,063 have a higher value than opportunity-threat. This shows that the optimization of strenght and opportunity in the development of corporate strategy.